Penerapan Model Rational Unified Process (RUP) Dalam Membangun Aplikasi Promosi dan Penjualan Berbasis Web (Studi Kasus: Toko Mie Ayam “Neng Kene Kiyeh”) - Chandra, Yudi Irawan; Irawati, Diyah Ruri; Riastuti, Marti (Fakultas Teknik Universitas Persada Indonesia YAI, 2024)
This research discusses the application of the Rational Unified Process (RUP) Model in thedevelopment of web-based promotion and sales applications, with a case study at the Chicken Noodle Shop“Neng Kene Kiyeh”. The purpose of this research is to design and implement applications that can increasethe efficiency of promotion and sales of chicken noodle products through digital platforms. The RUPmethod was chosen because of its iterative approach and focus on user needs, allowing for more structuredand controlled software development. The RUP model consists of four main phases: inception, elaboration,construction, and transition. In the inception phase, a needs identification and feasibility study are conductedto ensure that the application to be developed matches the business needs of the store. The elaboration phaseinvolves more in-depth analysis and system design, including use case modeling, risk analysis, andapplication architecture design. In the construction phase, application development is carried out with aniterative approach, allowing for improvements and adjustments based on user feedback. The transitionphase involves application testing and end-user training, as well as full system implementation. The result ofthis research is a web application that has main features such as product catalog, online ordering system, inventory management, and integrated digital promotion. The implementation of this application is expectedto increase the visibility of Chicken Noodle Shop “Neng Kene Kiyeh” in the digital market, simplify theordering process for customers, and increase sales. The trial shows that this application can function asexpected, and provides significant benefits in the store's operational processes. The conclusion of thisresearch is that the application of the RUP model can be an effective approach in building web-basedpromotional and sales applications, with a focus on meeting user needs and improving businessperformance.